Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome. Diagnostic and therapeutic approach of a rare disease (Colombia Medica, 2024)
Introduction: The Mayer-Rokitansky-Küster-Hauser syndrome is characterized by the absence of the vagina and uterus and primary amenorrhea.Objective: The diagnostic evaluation and the therapeutic possibilities of a rare syndrome.Materials and methods: We present a case of a Rokitansky syndrome.Results: The patient presented normal development of secondary sexual characters. Analysis also showed normal hormonal function behavior along with a 46, XX karyotype. Magnetic resonance imaging revealed uterine agenesis and treatment was delayed until the patient and her family understood the diagnosis.Conclusions: The diagnostic suspicion is the milestone to manage this disease. Physical exploration, hormonal function, and radiological studies must confirm this syndrome. Laparoscopy is the approach of choice.